Resilience to Climate Change by Biocontrol Yeasts Against Ochratoxin A Production in Robusta Coffee - Claudia López-Rodríguez; Carol Verheecke-Vaessen; Caroline Strub; Angélique Fontana; Tagro Guehi; Sabine Schorr-Galindo; Angel Medina (Toxins)
Aspergillus carbonarius is the main producer of Ochratoxin A (OTA) in coffee. In the last few years, there has been an increasing interest in using yeast isolates as Biocontrol Agents to prevent OTA production in coffee cherries during the primary postharvest processing. Little is known about how climate change abiotic conditions of increased temperature (+2–4 °C), elevated CO2 (existing levels of 400 vs. 1000 ppm), and increased drought stress will impact biocontrol resilience. This study examined the effect of a three-way interaction between temperature (27, 30, and 33 °C) x water activity (aw) (0.90 and 0.95 aw) x CO2 level (400 vs. 1000 ppm) on the growth and OTA production of A. carbonarius and the resilience of three yeast strains’ biocontrol capacity on fresh coffee cherries. High aw (0.95), CO2, and temperature levels increased the production of OTA by A. carbonarius. All the yeast biocontrol strains significantly reduced A. carbonarius growth by at least 20% and OTA production by up to 85%. From the three strains used, the Meyerozyma caribbica strain (Y4) showed the best resilience to climate change, since it reduced both growth (50%) and OTA production (70%) under future scenarios of CO2 and aw at all temperatures tested, and should be the one selected for pilot scale experiments in Ivory Coast.